Чехов в жизни: сюжеты для небольшого романа / Игорь Сухих - Сухих Игорь Николаевич (Диалог, 2011)
Экземпляры: аб. (2012) / Инвентарный номер: 54186 / Цена: / Сис.шифр: 83.3(2Рос=Рус)1 / Авт.знак: С 91 / ГРНТИ: 17.09 / ББК: 83.3(2Рос=Рус)1